2014
DOI: 10.1111/ncmr.12041
|View full text |Cite
|
Sign up to set email alerts
|

When Should We Disagree? The Effect of Relationship Conflict on Team Identity in East Asian and North American Teams

Abstract: Along with recent research uncovering distinctly Asian approaches to conflict management, we examine the experience and effect of relationship conflict on team identity in culturally homogeneous North American versus East Asian teams. In a longitudinal field experiment with student teams, we found that East Asian teams, compared to North American teams, experienced more relationship conflict at later stages of team tenure. We further found that, while relationship conflict undermined team identity in North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In line with Liang et al. (), our results suggest that group conflict is only detrimental to group performance in North American teams, but not East Asian teams.…”
Section: Study 2 Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with Liang et al. (), our results suggest that group conflict is only detrimental to group performance in North American teams, but not East Asian teams.…”
Section: Study 2 Resultssupporting
confidence: 92%
“…One possible reason the interaction was not significant is that our no‐faultline condition included both East Asian and Caucasian Canadian ethnically homogeneous groups. Liang, Adair, and Hideg () recently argued that the temporal experience and consequences of intragroup conflict vary depending on a group's cultural identity. They found that relationship conflict undermined team identity in North American teams but not in East Asian teams.…”
Section: Study 2 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, we would expect collectivism to be activated in a group setting for East Asians, but the effect of cultural collectivism is uncertain. Westwood and Low (2003) argue that commitment to harmony and group goals in collectivist cultures might temper possible negative effects of group conflict, a view supported by Liang, Adair, and Hideg’s (2014) research on conflict in East Asian versus Caucasian Canadian teams. In other words, if collectivist values promote cohesion and group safety that facilitate sharing revolutionary ideas, high collectivism values in East Asian teams could promote novelty through psychological safety, while in Western teams low collectivism values could promote novelty through greater comfort with individual self-expression and divergent thinking.…”
Section: Discussionmentioning
confidence: 99%
“…"Experiment" is a mislabel that too often slips by reviewers and editors. Calling nonexperimental or quasi-experimental research experimental or field-experimental is not uncommon (e.g., Azar et al 2013, Beer & Cannon 2004, Liang et al 2014, Mitchell et al 1997, Morgan et al 2013. Some of these articles reported case studies, which Bass et al (1976) called "a succession of tryouts-what 'experiments' used to be in the original sense of the word" (p. 355).…”
Section: Not Every "Experiment" Is An Experimentsmentioning
confidence: 99%